Mitochondrial aberrations during the progression of disuse atrophy differentially affect male and female mice. Issue 6 (29th September 2021) - Rosa‐Caldwell, Megan E.; Lim, Seongkyun; Haynie, Wesley S.; Brown, Jacob L.; Lee, David E.; Dunlap, Kirsten R.; Jansen, Lisa T.; Washington, Tyrone A.; Wiggs, Michael P.; Greene, Nicholas P.
Abstract: Background: Disuse decreases muscle size and is predictive of mortality across multiple pathologies. Detriments to mitochondrial function are hypothesized to underlie disuse‐induced muscle atrophy. Little data exist on early mechanisms contributing to onset of these pathologies, nor is it known how they differ between sexes. The purpose of this study was to examine differential and conserved responses to mitochondrial quality control in male and female mice during the development and progression of disuse‐induced atrophy. Methods: One hundred C57BL/6J mice (50 male and 50 female) were hindlimb unloaded to induce disuse atrophy for 0 (con), 24, 48, 72, or 168 h. At designated time‐points, extensor digitorum longus, gastrocnemius, and soleus muscles were collected for analysis of mitochondrial quality control markers. Results: One hundred sixty‐eight hours of disuse resulted in ~25% lower oxidative muscle fibre CSA in both male ( P  = 0.003) and female ( P  = 0.02) mice without any differences due to disuse in glycolytic fibres. In male mice, 48 h of unloading was sufficient to result in ~67% greater mitochondrial oxidative stress as assessed by the reporter gene pMitoTimer compared with 0 h ( P  = 0.002), this mitochondrial stress preceded detectable muscle loss. However in female mice, mitochondrial oxidative stress did not occur until 168 h of disuse (~40% greater mitochondrial oxidative stress in 168 h compared with 0 h of disuse, P  < 0.0001). Blunted oxidative stress in female mice appeared to coincide with greater inductions of autophagy and mitophagy in female mice (~3‐fold greater BNIP3 and ~6‐fold greater LC3II/I ratio P  < 0.0001 and P  = 0.038 respectively). Male mice overall had greater reactive oxygen species (ROS) production compared with female mice. Female mice had a greater induction of ROS within 24 h of disuse (~4‐fold greater compared with 0 h, P  < 0.0001); whereas male mice did not have greater ROS production until 168 h of disuse (~2‐fold greater, P  < 0.0001). Although all muscle types exhibited some alterations to mitochondrial quality control, such as increased markers of mitophagy and fission, the soleus muscle in both male and female mice exhibited consistent alterations to various markers of mitochondrial quality. Markers of mitochondrial translation were approximately 30–50% lower within 24 h of unloading in both male and female soleus muscle ( P value ranges: <0.0001–0.03). Conclusions: Disuse negatively affects mitochondria differentially between sexes during development of muscle wasting. Acutely, female mice may forgo muscle mass to maintain mitochondrial quality compared with male mice. These differences may contribute to divergent clinical manifestations of atrophy.